2018
DOI: 10.2741/4610
|View full text |Cite
|
Sign up to set email alerts
|

Homeostatic regulation of plasma amino acid concentrations

Abstract: One major goal of nutrition is to maximize the rate of muscle protein gain via provision of amino acids (AAs) through blood plasma. Comparing the plasma AA concentrations with the growth performance data can help to elucidate the metabolic mechanisms regulating plasma AA homeostasis, nutrient utilization, and intracellular protein turnover. Knowledge about the homeostatic regulation of plasma AA profile can aid in predicting dietary AA availabilities, the order of limiting AAs, and the whole body protein metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 68 publications
0
26
0
Order By: Relevance
“…Using dietary non-protein nitrogenous substances, such as urea, ammonium, mucins, as well as the enzymatic secretions and sloughed epithelial cells of the host, the microbiota in pig intestine can also synthesize AAs and proteins for incorporation into bacterial cells (25, 51). It was revealed that the small intestine is also the major site for the microbe-derived AA absorption, and some investigators suggested that the biosynthesis of AAs and proteins by the microbiota in the host GIT partake in the regulation of AA homeostasis of the host (25, 54). However, the intestinal microbiota do not make a significant contribution of AAs to the host since pig exhibits a negative nitrogen balance when fed an AA- or protein-free diet (25).…”
Section: Effects Of Amino Acids On Gut Health and Functionsmentioning
confidence: 99%
“…Using dietary non-protein nitrogenous substances, such as urea, ammonium, mucins, as well as the enzymatic secretions and sloughed epithelial cells of the host, the microbiota in pig intestine can also synthesize AAs and proteins for incorporation into bacterial cells (25, 51). It was revealed that the small intestine is also the major site for the microbe-derived AA absorption, and some investigators suggested that the biosynthesis of AAs and proteins by the microbiota in the host GIT partake in the regulation of AA homeostasis of the host (25, 54). However, the intestinal microbiota do not make a significant contribution of AAs to the host since pig exhibits a negative nitrogen balance when fed an AA- or protein-free diet (25).…”
Section: Effects Of Amino Acids On Gut Health and Functionsmentioning
confidence: 99%
“…A number of studies have described homeostatic regulation of plasma free amino acids (AA) and related metabolites [ 5 ] to help in maximizing protein accretion and growth of pigs, but few have tried to identify early plasma and/or blood markers that will predict animals susceptible to poor growth [ 6 ]. The present study enlightens a set of relevant blood immune and metabolic variables for whom range of variations between two times in an early period of growth (first 3 weeks of the test period) was able to explain the relative ADG during the whole test period (rADG W0-W6 ).…”
Section: Discussionmentioning
confidence: 99%
“…These differences in carcass and muscle indispensable AA composition were not reflected in circulating levels of plasma free AA with some exceptions (lysine, threonine and methionine), although the sum of indispensable, dispensable and total AA was always higher in the LDW pigs, according to their higher protein pool. However, relations among these different AA pools are complex as plasma AA concentration is the result of inputs from dietary intake and AA released by tissues (proteolysis and de novo synthesis, mainly by muscle), and outputs to AA oxidation and metabolism (synthesis of proteins and other molecules; see review by Liao, Regmi, & Wu, ).…”
Section: Discussionmentioning
confidence: 99%